Foreign direct investment in the banking sector of Kazakhstan - N. A. Turgenbayev; A. K. Kantarbayeva (Экономика: стратегия и практика, 2020)
This article investigates the mechanisms of investing into Kazakhstan through banking innovations, assesses the current standing and the role of foreign subsidiary banks in the existing macroeconomic ecosystem in the region, and studies the perspectives of attracting new players in line the full membership of Kazakhstan into WTO. In addition to that, the purpose of this exercise is to hypothetically evaluate the effects of the current negative global economy trends on the banking system of Kazakhstan.